Distortion Analysis of Active Filters. (1988) - Kumar, Umesh; Shukla, Sushil Kumar
Abstract : Second order active filters using single and two operational amplifiers at high frequencies and/or large-signal levels are investigated for their nonlinear performance. A general procedure using the Volterra series in presented regarding intermodulation distortion. Computer results by implementation in a program "Distortion Analysis" demonstrate the accuracy of the analysis technique.